STUDENTS’ PERCEPTIONS ON THE USE OF PAPERRATER FOR ESSAY WRITING FEEDBACK - Salsabila, Rohiidah; Aridah, Aridah; Setiawan, Iwan (Universitas Islam Sumatera Utara (UISU), 2025)
This study investigates how EFL students perceive the use of PaperRater as an automated feedback tool in essay writing. Although Grammarly and ChatGPT have received significant attention, PaperRater remains underexplored. Using a qualitative narrative inquiry approach, three Indonesian undergraduate students shared their experiences via interviews and by submitting annotated drafts for analysis. The results show that PaperRater helped them improve grammar, vocabulary, and sentence structure by providing quick feedback that encouraged independent revision. However, they also faced several challenges, such as unclear suggestions, occasional inaccuracies, and the tool’s inability to address more complex writing aspects like argument development and coherence. Although some students initially found the interface confusing, they gradually became more comfortable using it. Overall, PaperRater was seen as a helpful tool for correcting surface-level errors, but it still needed to be combined with teacher feedback and other tools to support deeper writing improvement. This study emphasizes the importance of using automated tools thoughtfully and in balance with human guidance. Further research with a larger group of participants is recommended to explore long-term effects.